CONCEPTS AND EXPERIENCES OF IMPRISONED WOMEN ABOUT VIOLENCE - Zeyne Alves Pires Scherer; Edson Arthur Scherer (Universidade Federal do Paraná, 2009)
This research aimed to describe the concepts and experiences of imprisoned women about violence. It is anexploratory descriptive study. Semi-structured interviews were held with 15 imprisoned women. In the analysis of answersto the question "What is violence to you?" two categories emerged: "concepts and violence experiences in society", theyconsidered as violence: physical aggressions, sexual abuses, homicides and psychological abuse, inside (with theconnivance of family members) or outside the domestic environment. The context of violence that many of these womenexperienced includes a chain of multiple legitimated exclusions, as drug traffic for example. The category "concepts andviolence experiences in prison" includes experiences in prison defined as suffering physical and psychological aggressionsand privation of liberty. The permanent contact with violence interferes in their perspective of life. Building public policiesagainst violence in primary care is suggested, especially at home, where the cycle seems to start.